Neural mechanisms underlying the effects of physical fatigue on effort-based choice - Patrick S. Hogan (Nature Portfolio, 2020)
Fatigue influences our choices to engage in physical activity. Here, the authors investigate the underlying cognitive and neuronal mechanisms by which fatigue influences decisions to exert, and show that information about motor cortical state modulates decisions to engage in physical activity.